'Surprise' lambs 18 months after sterilisation of a teaser ram. Issue 1 (15th February 2019) - Morrell, Jane M; Wallgren, Margareta
Abstract : The owner of a flock of a phenotypically distinct sheep breed purchased a 'sterilised' teaser ram to mark oestrus ewes for mating with purebred rams. Lambing in the subsequent year proceeded as planned. The following year, three of 30 ewes marked by the teaser produced lambs that were not phenotypically purebred and DNA analysis revealed with 99 per cent certainty that the teaser ram was the sire. During a postmortem examination of the scrotal contents, the following findings were noted. The testes were adherent to the scrotum and were not freely movable. The cauda epididymis had been removed on both sides; macroscopically there was no connection between the corpus epididymis and the vas deferens on either side. However, a drop of creamy fluid was expressed from the right vas deferens, which contained fully mature spermatozoa. An anastomosis must have formed between the corpus epididymis and vas deferens after the operation.